EKSISTENSI PETUGAS KAMPANYE MENURUT UNDANG-UNDANG PEMILIHAN UMUM DAN PERATURAN KPU NOMOR 15 TAHUN 2023 - Darusman S, Chandra; Djusfi, Apri Rotin; Thariq, Phoenna Ath; Maulana, Jefrie (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
Campaigning is one of the stages in the general election. Campaign implementation can be carried out by campaign executives, election participants, campaign teams, and campaign officers. However, the existence of campaign officers is not regulated in the Election Law but only regulated in KPU Regulation Number 15 of 2023. This has the potential to cause legal problems related to the accountability of campaign officers according to the law. This research is a normative juridical research with a statutory approach. From the research conducted, it is known that campaign officers cannot be held criminally liable if they commit prohibited actions in the process of conducting campaigns. This is because there is no formulation of legal norms in the Election Law that recognizes, recognizes and regulates the existence of campaign officers. The implementation of criminal law accountability must guide the principle of legality which is one of the fundamental principles in criminal law.